Diversity of nematodes population in cumin (Cuminum cyminum) crop in semi arid regions of Rajasthan, India - KANT, KRISHNA; SINGH, BALRAJ; SHARMA, Y K; MEENA, S R; SOLANKI, R K; MISHRA, B K; MEENA, N K; SIDDIQUI, A U (The Indian Journal of Agricultural Sciences, 2017)
The survey was conducted in cumin crop at farmer’s field of Ajmer district of Rajasthan, India during 2013-14 and 2014-15 to assess the crop suffered from multiple nematodes infestation. Total 90 cumin (Cuminum cyminum L.) plant samples were collected in two years from 18 villages across 5 development blocks. Among all collected samples, 63 were found infested with different species of nematodes. Highest numbers of samples contain nematodespopulations recorded from Pisangan block of Ajmer district, whereas minimum number of samples infested with nematodes population was found in Kekri block. There were three different species of nematodes associated with cumin root namely Pratylenchus thornei, Hoplolaimus indicus and Meloidogyne incognita. The nematode species P. thornei and H. indicus were found for first time in cumin field causing damage to the root of the plant.